Pengaruh Manajemen Laba Akrual dan Strategi Bisnis terhadap Risiko Kebangkrutan: Peran Moderasi Tata Kelola Perusahaan di Indonesia: Indonesia - Agatha, Steffani Maria; Fathoni, Muhammad Ihtifazhuddin Rizki (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study examines the influence of accrual-based earnings management and business strategy on bankruptcy risk among publicly listed companies in Indonesia, with corporate governance serving as a moderating variable. In an increasingly complex business environment, bankruptcy risk is driven not only by external factors but also by internal practices, such as financial statement manipulation. Drawing on agency and signaling theories, the study explores how strategies like cost leadership and differentiation, along with effective governance, affect the likelihood of bankruptcy. The findings are expected to contribute to academic literature and provide practical insights for managers, investors, and regulators in developing more accurate and context-specific bankruptcy risk detection mechanisms.